2006
DOI: 10.1177/0961203306071919
|View full text |Cite
|
Sign up to set email alerts
|

Infections in systemic lupus erythematosus: a prospective and controlled study of 110 patients

Abstract: We decided to analyse the incidence and characteristics of infection in systemic lupus erythematosus (SLE) and determine the related risks factors. One-hundred and ten SLE patients and 220 controls were prospectively followed up over three years and all the infectious episodes were recorded. A case-control design was established to identify risk factors of infection. Thirty-nine SLE patients suffered at least one infection (36%) versus 53 controls (22%), RR = 1.63 (P < 0.05). The incidence of urinary infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
126
2
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(175 citation statements)
references
References 24 publications
20
126
2
23
Order By: Relevance
“…Prednisone treatment, even at moderate doses, increases the risk, whilst antimalarials have a protective effect [13]. In detail, it was shown that the prednisone dose at the time of the event had a facilitating effect on infections, in agreement with previous studies [9], [10] and [11]. Moreover, it is worthy of note that the median dose of patients with major infections was only 7.5 mg day−1, with an 11-times higher risk of suffering a serious infection for each increase of 10-mg day−1 prednisone.…”
Section: Predictors Of Major Infections In Slesupporting
confidence: 88%
See 1 more Smart Citation
“…Prednisone treatment, even at moderate doses, increases the risk, whilst antimalarials have a protective effect [13]. In detail, it was shown that the prednisone dose at the time of the event had a facilitating effect on infections, in agreement with previous studies [9], [10] and [11]. Moreover, it is worthy of note that the median dose of patients with major infections was only 7.5 mg day−1, with an 11-times higher risk of suffering a serious infection for each increase of 10-mg day−1 prednisone.…”
Section: Predictors Of Major Infections In Slesupporting
confidence: 88%
“…Several studies have analysed the prevalence and associated clinical and laboratory features of infection in SLE *[8], [9], [10] and [11]. Common themes are medications, including use of steroids and/or cyclophosphamide or high-disease activity as measured by the SLE Disease Activity Index [12].…”
Section: Predictors Of Major Infections In Slementioning
confidence: 99%
“…Patients suffering from systemic lupus erythematosus (SLE), rheumatoid arthritis (RA) and other autoimmune rheumatic diseases have a significantly higher risk of developing various infections compared to the healthy population (Bosch et al 2006;Glück and Müller-Ladner 2008). Infections are one of the leading causes of mortality in these patients (Doran et al 2002;Cervera et al 2003;Falagas et al 2007).…”
mentioning
confidence: 99%
“…В последние годы все большее внимание привлекает проблема пневмоний, вызванных Pneumocystis jirovecii. По данным метаанализа, пневмоци-стная пневмония была обнаружена у 5% больных СКВ [42]. Предполагается, что в качестве факторов риска раз-вития пневмоцистной пневмонии среди пациентов с СКВ следует рассматривать высокую активность, пато-логию почек, интерстициальный легочный фиброз, большую суточную дозу ГК.…”
Section: Discussionunclassified